2020
DOI: 10.3390/cancers12051120
|View full text |Cite
|
Sign up to set email alerts
|

The Validity and Predictive Value of Blood-Based Biomarkers in Prediction of Response in the Treatment of Metastatic Non-Small Cell Lung Cancer: A Systematic Review

Abstract: With the introduction of targeted therapies and immunotherapy, molecular diagnostics gained a more profound role in the management of non-small cell lung cancer (NSCLC). This study aimed to systematically search for studies reporting on the use of liquid biopsies (LB), the correlation between LBs and tissue biopsies, and finally the predictive value in the management of NSCLC. A systematic literature search was performed, including results published after 1 January 2014. Articles studying the predictive value … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 148 publications
0
8
0
Order By: Relevance
“…The differences and dissimilarity might be attributed to the sampling time: most tissue specimens were tested with the orthotopic resection, while blood was typically sampled following a series of therapeutic contacts. 17 Blood specimens might be more suitable for determining the extremely rare EGFR variants, such as E709K, L747S, D761Y, T854A, L861R, etc, relative to tissue specimens, although there were no statistical differences between the two specimens.…”
Section: Resultsmentioning
confidence: 98%
“…The differences and dissimilarity might be attributed to the sampling time: most tissue specimens were tested with the orthotopic resection, while blood was typically sampled following a series of therapeutic contacts. 17 Blood specimens might be more suitable for determining the extremely rare EGFR variants, such as E709K, L747S, D761Y, T854A, L861R, etc, relative to tissue specimens, although there were no statistical differences between the two specimens.…”
Section: Resultsmentioning
confidence: 98%
“…A liquid biopsy sample consists of different (circulating) components derived from cancer as well as from healthy tissue. In this review, the characteristics of the following components will be discussed: circulating cell-free DNA (cfDNA), circulating tumor cells (CTCs), extracellular vesicles (EVs), epigenetic signatures, microRNA (miRNA), volatile organic compounds (VOCs) and the gut microbiota (Table 1, Figure 1) [20,21]. Despite the potential benefits, major hurdles need to be overcome.…”
Section: Liquid Biopsymentioning
confidence: 99%
“…ctDNA assays have shown high agreement with tumor tissue genotyping, particularly when samples are temporally matched. In lung cancer, evidence of prognostic and predictive value is available for monitoring of the human epidermal growth factor receptor T790M ( EGFR T790M ) resistance to EGFR tyrosine kinase inhibitors ( EGFR -TKI) [ 26 ], as reflected by the FDA approval for the Cobas EGFR mutation test in 2016 [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most studies have evaluated quantitative ctDNA as a prognostic marker for survival following curative treatment or aimed to guide decisions in the (neo-) adjuvant setting in colorectal, breast, lung, bladder and pancreatic cancer and melanoma [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. In addition, a few systematic reviews have identified evidence levels for a range of circulating tumor markers, including cells, proteins, DNA and RNA, in lung and breast cancer, respectively [ 26 , 39 ]. For breast cancer, about 70 of the 320 studies reviewed investigated the clinical validity or utility of either CTCs or proteins in prospective studies [ 39 ].…”
Section: Introductionmentioning
confidence: 99%